2010
DOI: 10.1073/pnas.1002910107
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Cf resistance proteins mediate recognition of cognate homologous effectors from fungi pathogenic on dicots and monocots

Abstract: Most fungal effectors characterized so far are species-specific and facilitate virulence on a particular host plant. During infection of its host tomato, Cladosporium fulvum secretes effectors that function as virulence factors in the absence of cognate Cf resistance proteins and induce effector-triggered immunity in their presence. Here we show that homologs of the C. fulvum Avr4 and Ecp2 effectors are present in other pathogenic fungi of the Dothideomycete class, including Mycosphaerella fijiensis, the causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
216
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(218 citation statements)
references
References 40 publications
2
216
0
Order By: Relevance
“…These previous studies and our work here reiterate that CfAvr4 possesses a chitinase protection activity also seen for Mg1LysM and Mg3LysM. Moreover, recent studies on sequenced fungal genomes identified homologs of the CfAvr4 gene in other Mycosphaerellaceae species, namely Mycosphaerella fijiensis and several Cercospora species (Stergiopoulos et al, 2010). However, perhaps significantly, no Avr4 homologs were identified in the M. graminicola genome, which may explain why, in contrast to C. fulvum Ecp6, LysM effectors of M. graminicola may have evolved additional functions that serve to protect fungal hyphae against plant hydrolytic enzymes.…”
Section: Mglysm Proteins Have Additional Putative Effector Functions mentioning
confidence: 57%
“…These previous studies and our work here reiterate that CfAvr4 possesses a chitinase protection activity also seen for Mg1LysM and Mg3LysM. Moreover, recent studies on sequenced fungal genomes identified homologs of the CfAvr4 gene in other Mycosphaerellaceae species, namely Mycosphaerella fijiensis and several Cercospora species (Stergiopoulos et al, 2010). However, perhaps significantly, no Avr4 homologs were identified in the M. graminicola genome, which may explain why, in contrast to C. fulvum Ecp6, LysM effectors of M. graminicola may have evolved additional functions that serve to protect fungal hyphae against plant hydrolytic enzymes.…”
Section: Mglysm Proteins Have Additional Putative Effector Functions mentioning
confidence: 57%
“…Indeed, Ecp6, a secreted effector from the tomato pathogen Cladosporium fulvum (synonym Passalora fulva), was until recently among the very few fungal effectors with homologs in numerous other fungi, mainly due to the presence of LysM domains in this protein, a motif that is widespread among microbes of diverse taxa and lifestyles (Bolton et al, 2008;de Jonge and Thomma, 2009). At the same time, we have also shown that homologs of the Avr4 and Ecp2 effectors from C. fulvum are present in some phylogenetically related species of Dothideomycetes and beyond (Stergiopoulos et al, 2010(Stergiopoulos et al, , 2012. Why some effectors are broadly conserved while others are not is poorly understood, but we have hypothesized that core fungal effectors may have conserved virulence functions that facilitate infections on a wide range of hosts.…”
Section: Introductionmentioning
confidence: 68%
“…Why some effectors are broadly conserved while others are not is poorly understood, but we have hypothesized that core fungal effectors may have conserved virulence functions that facilitate infections on a wide range of hosts. Alternatively, given their broad distribution in fungi with diverse lifestyles, including pathogens and nonpathogens, core effectors may also serve roles beyond deregulation of host immunity during infections, as for example interactions with other microbes in a pathogen's environment (Stergiopoulos et al, 2010(Stergiopoulos et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Avr4 homologs have also been identified in several other fungal species, including Mycosphaerella fijiensis (Stergiopoulos et al 2010) and Dothistroma septosporum (De Wit et al 2012). However, functional homologs of Ecp6 were found in Zymoseptoria tritici (Mg3LysM) and Magnaporthe oryzae (Slp1) (De Jonge et al 2010; Marshall et al 2011; Mentlak et al 2012).…”
Section: Fungal Potential Against Host Immune Systemmentioning
confidence: 99%
“…Stergiopoulos et al (2010), based on their work in M. fijiensis (Black Sigatoka, the most significant disease of bananas and plantains), proposed a function for Ecp2 (functional homolog of Ecp6) and Avr4. In the absence of Cf resistance proteins, Ecp2 promoted virulence by interacting with an in-planta target, causing host cell necrosis that facilitates the necrotrophic mode of nutrition of hemibiotrophs, such as M. fijiensis .…”
Section: Fungal Potential Against Host Immune Systemmentioning
confidence: 99%